Multicultural-Based PAI Management Quality Management In Islamic Educational Institutions - Arifin, Ince Anshar H; Adilah, Nur; Supriandi, Supriandi (Journal of Indonesian Progressive Education, 2026)
Multicultural-based Islamic Religious Education (PAI) management is a strategic approach in the administration of Islamic education that focuses on improving the quality of education while simultaneously strengthening inclusive and moderate religious attitudes. This research aims to theoretically examine the concept of multicultural-based Islamic Religious Education (PAI) management, the application of quality management in Islamic education, and its implications for the improvement of the quality of Islamic educational institutions. This research uses a qualitative approach with a literature study type (library research) thru the search and analysis of books, national and international journal articles, as well as relevant academic documents. Data analysis was conducted using content analysis and thematic analysis techniques to identify patterns, concepts, and key principles related to multicultural-based Islamic Education Management (PAI). The study results indicate that multicultural-based PAI management views diversity as a strategic potential in improving the quality of Islamic education. The integration of multicultural values in the PAI quality management system contributes to the development of contextual curricula, inclusive and dialogical learning, strengthening educator professionalism, and the formation of a democratic and virtuous culture in Islamic educational institutions. Thus, multicultural-based PAI management not only functions as an administrative instrument but also as a pedagogical and ideological strategy in shaping students who are religious, tolerant, and socially responsible in a multicultural society.